Childhood externalizing and internalizing psychopathology in the prediction of early substance use - King, Serena M.; Iacono, William G.; McGue, Matt (Addiction (Abingdon, England), 2004)
ABSTRACT Aims  To examine the prospective relationships between childhood externalizing and internalizing disorders and substance use in early adolescence. Design  Longitudinal, community‐based study of twins (aged 11 at intake; aged 14 at follow‐up). Setting and participants  The sample was composed of twins participating in the Minnesota Twin Family Study, an epidemiological sample of twins and their families representative of the state population of Minnesota. A total of 699 twin girls and 665 twin boys participated at both time‐points. Measurements  Twins participated in in‐person, life‐time diagnostic assessments of the following childhood DSM III‐R externalizing and internalizing disorders at age 11: conduct disorder, oppositional defiant disorder, attention deficit hyperactivity disorder, major depressive disorder and in addition, for girls only, overanxious disorder and separation anxiety disorder. At ages 11 and 14, substance use and abuse were assessed. Findings  Externalizing psychopathology predicted having tried alcohol, nicotine and cannabis by age 14 as well as regular and advanced experience with these substances. Internalizing disorders showed weak effects, with only major depression at age 11 showing a significant relationship with substance use at age 14. Conclusion  The results suggest that externalizing psychopathology is a robust prospective predictor of a variety of early onset substance use behaviors and is systematically related to degree of substance use involvement. The results also suggest that depression may predict initiation of licit substance use in early adolescence.